Investigation of Dark and Bright Soliton Solutions of Some Nonlinear Evolution Equations - Demiray, Seyma Tuluce; Bulut, Hasan (E D P Sciences, 2018)
In this paper, generalized Kudryashov method (GKM) is used to find the exact solutions of (1+1) dimensional nonlinear Ostrovsky equation and (4+1) dimensional Fokas equation. Firstly, we get dark and bright soliton solutions of these equations using GKM. Then, we remark the results we found using this method.
3rd International Conference on Computational Mathematics and Engineering Sciences (CMES) -- MAY 04-06, 2018 -- Final Int Univ, Girne, CYPRUS
Keywords: Traveling-Wave Solutions; Multisoliton Solutions